2021
DOI: 10.1021/acs.nanolett.1c00600
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Near-Infrared Emission Range of Indium Phosphide Quantum Dots for Multiplexed In Vivo Imaging

Abstract: This report of the reddest emitting indium phosphide quantum dots (InP QDs) to date demonstrates tunable, near-infrared (NIR) photoluminescence (PL) as well as PL multiplexing in the first optical tissue window while avoiding toxic constituents. This synthesis overcomes the InP "growth bottleneck" and extends the emission peak of InP QDs deeper into the first optical tissue window using an inverted QD heterostructure, specifically ZnSe/InP/ZnS core/shell/shell nanoparticles. The QDs exhibit InP shell thickness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…By introducing HgS interlayer at the core/shell CdSe@CdS QDs interface, the visible emitters can be converted into highly efficient NIR fluorophores by Klimov (Sayevich et al, 2021). Dennis also reported the similar ZnSe@ InP@ZnS core/shell/shell heterostructure, in which tunable emission ranging from visible to NIR wavelengths can be obtained by changing the InP interlayer thickness (Figure 3C; Saeboe et al, 2021). Through well-designed core-shell structure, doping different ions, and surface modification the NIR emissions QDs with biocompatible properties can be achieved.…”
Section: Frontiers Inmentioning
confidence: 96%
See 1 more Smart Citation
“…By introducing HgS interlayer at the core/shell CdSe@CdS QDs interface, the visible emitters can be converted into highly efficient NIR fluorophores by Klimov (Sayevich et al, 2021). Dennis also reported the similar ZnSe@ InP@ZnS core/shell/shell heterostructure, in which tunable emission ranging from visible to NIR wavelengths can be obtained by changing the InP interlayer thickness (Figure 3C; Saeboe et al, 2021). Through well-designed core-shell structure, doping different ions, and surface modification the NIR emissions QDs with biocompatible properties can be achieved.…”
Section: Frontiers Inmentioning
confidence: 96%
“…Reproduced with permission from Bruns et al (2017) . (C) NIR emission ZnSe/InP/ZnS core/shell/shell nanoparticles and their bandgap alignments with corresponding electron and hole wave functions ( Saeboe et al, 2021 ). Reproduced with permission from Dennis et al (2021).…”
Section: Emission Mechanism Of Near-infrared Inorganic Nanomaterialsmentioning
confidence: 99%
“…In a mouse model using multiplexed lymph node imaging, Saeboe et al reported the reddest emitting indium phosphide quantum dots (InPQDs) to date. In the first optical tissue window, they exhibited tunable NIR photoluminescence (PL) as well as PL multiplexing while avoiding hazardous components (68). By widening the range of controllable direct-bandgap emission from InP-based nanostructures, these nanoparticles efficiently overcome a synthetic barrier that has stopped InPQDs from reaching their full potential.…”
Section: Qds For In Vivo Imagingmentioning
confidence: 99%
“…example, in a recent study, Saeboe et al performed multiplexed in vivo imaging in NIR-I using ZnSe/InP/ZnS SNCs (Figure5 -B) 55. The clever core/multi-shell architecture and the resulting band scheme induced localization of the electron's wavefunction at the ZnSe core and the holes at the first InP shell, in turn pushing the emission of InP deeper into the NIR (Figure5-B1).…”
mentioning
confidence: 97%